PENCEGAHAN PENYEBARAN COVID 19 DENGAN PENERAPAN TEKNOLOGI OZON - Puji Laksmini; Muhammad Aris Risnandar; Yusup Supriyono; Enov Tikupasang; Nurul Hiron (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The West Java Government has categorized Tasikmalaya be at level 4 (heavy) related to the spread of Covid-19. Community Health Centre of Cibeureum provides health services for the community in Cibeureum District, covering 5 villages. Community Health Centre of Cibeureum provides hospitalization . The average pre-Covid visitasion was 150-200 patients per day, then during the Covid period it decreased to 50-70 patients per day. During the PSBB period, employees of the Community Health Centre of Cibeureum have experienced significant changes in work psycholog, because in addition to having the obligation to serve community, employees were worried about exposure to the Covid-19 virus. There are various kinds of air sterilization methods, including using high pressure : both positive and negative, ultraviolet light, HEPA, and ozone. Apart from being used as an antiseptic, ozone has antiviral, antifungal, and antiprotozoal functions. On the other hand, ozone can also have adverse health effects if used without using standard regulations.